The Social Effects of Economic Adjustment on Arab Countries. (International Monetary Fund, 1997)
The papers presented in this volume edited by Taher H. Kanaan - the eighth in a series of seminars sponsored by the Arab Fund for Economic and Social Development, the Arab Monetary Fund, the IMF, and the World Bank - explore the relationship between economic reforms, growth, employment, and social sector performance. Topics discussed include the political and social dimensions of policies privatization in the social sectors, social safety nets, poverty and the poor, and women, poverty, and population growth.